PENGARUH KEPRIBADIAN DAN KERJASAMA TIM TERHADAP KINERJA INSTRUKTUR RUMAH SAKIT PENDIDIKAN (TEACHING HOSPITAL) DI KOTA JAKARTA TIMUR - Seny Herna Wanty (Jurnal Manajemen Pendidikan, 2018)
The objective of the research is to find out the effect of personality and teamwork on instructor’s job performance. This research was conducted at Teaching Hospital in East Jakarta. This research was using a survey method with path analysis applied in testing hypothesis and 67 samples selected by simple random sampling. The research technique is analysis with quantitative research approaches by using causal analysis. The finding of the research are: (1) there is a positive direct effect of personality on job performance; (2) ) there is a positive direct effect of teamwork on job performance; (3) ) there is a positive direct effect of personality on teamwork.